Discourse and Power Relations: A Critical Discourse Analysis of a Pakistani Talk Show - Iqbal, Nayab; Azhar, Kaukab Abid; Shah, Zubair Ahmed (Journal of Pragmatics Research, 2020)
The paper aims at studying the ways power and inequality are enacted in a Pakistani talk show aired on Capital TV on 14th August 2019. The research primarily focused on analyzing turn-taking patterns of the discussion held between the host of the program and three guests. The analysis revealed the unequal distribution of turns implying the unequal distribution of power between the host and guests as well as between the guests. The host of the program through her discourse asserted power as she was the one to control the topic of discussion throughout the program. Her power can be attributed to the power of media. Besides, one of the guest speakers, Jawwad asserted his power through his knowledge. The female speaker did not have enough representation and was not given enough chance to share her views, therefore, it can be concluded that gender was another element that played an important part in forming the power relations in the discussion that was observed.Keywords: Critical Discourse Analysis, Discourse Power Relations, Media Discourse and Talk Shows, Turn-taking